Association Between Intraoperative Arterial Hypotension and Postoperative Delirium After Noncardiac Surgery: A Retrospective Multicenter Cohort Study. (13th September 2021) - Wachtendorf, Luca J.; Azimaraghi, Omid; Santer, Peter; Linhardt, Felix C.; Blank, Michael; Suleiman, Aiman; Ahn, Curie; Low, Ying H.; Teja, Bijan; Kendale, Samir M.; Schaefer, Maximilian S.; Houle, Timothy T.; et al.
Abstract : BACKGROUND: It is unclear whether intraoperative arterial hypotension is associated with postoperative delirium. We hypothesized that intraoperative hypotension within a range frequently observed in clinical practice is associated with increased odds of delirium after surgery. METHODS: Adult noncardiac surgical patients undergoing general anesthesia at 2 academic medical centers between 2005 and 2017 were included in this retrospective cohort study. The primary exposure was intraoperative hypotension, defined as the cumulative duration of an intraoperative mean arterial pressure (MAP) <55 mm Hg, categorized into and short (<15 minutes; median [interquartile range IQR], 2 [1–4] minutes) and prolonged (≥15 minutes; median [IQR], 21 [17–31] minutes) durations of intraoperative hypotension. The primary outcome was a new diagnosis of delirium within 30 days after surgery. In secondary analyses, we assessed the association between a MAP decrease of >30% from baseline and postoperative delirium. Multivariable logistic regression adjusted for patient- and procedure-related factors, including demographics, comorbidities, and markers of procedural severity, was used. RESULTS: Among 316, 717 included surgical patients, 2183 (0.7%) were diagnosed with delirium within 30 days after surgery; 41.7% and 2.6% of patients had a MAP <55 mm Hg for a short and a prolonged duration, respectively. A MAP <55 mm Hg was associated with postoperative delirium compared to no hypotension (short duration of MAP <55 mm Hg: adjusted odds ratio [ORadj ], 1.22; 95% confidence interval [CI], 1.11–1.33; P < .001 and prolonged duration of MAP <55 mm Hg: ORadj, 1.57; 95% CI, 1.27–1.94; P < .001). Compared to a short duration of a MAP <55 mm Hg, a prolonged duration of a MAP <55 mm Hg was associated with greater odds of postoperative delirium (ORadj, 1.29; 95% CI, 1.05–1.58; P = .016). The association between intraoperative hypotension and postoperative delirium was duration-dependent (ORadj for every 10 cumulative minutes of MAP <55 mm Hg: 1.06; 95% CI, 1.02–1.09; P =.001) and magnified in patients who underwent surgeries of longer duration ( P for interaction = .046; MAP <55 mm Hg versus no MAP <55 mm Hg in patients undergoing surgery of >3 hours: ORadj, 1.40; 95% CI, 1.23–1.61; P < .001). A MAP decrease of >30% from baseline was not associated with postoperative delirium compared to no hypotension, also when additionally adjusted for the cumulative duration of a MAP <55 mm Hg (short duration of MAP decrease >30%: ORadj, 1.13; 95% CI, 0.91–1.40; P = .262 and prolonged duration of MAP decrease >30%: ORadj, 1.19; 95% CI, 0.95–1.49; P = .141). CONCLUSIONS: In patients undergoing noncardiac surgery, a MAP <55 mm Hg was associated with a duration-dependent increase in odds of postoperative delirium. This association was magnified in patients who underwent surgery of long duration.